THE POLICIES UNDERLAYING THE RULES OF ENFORCEMENT OF FOREIGN JUDGMENTS IN LIBYA: A COMPARATIVE STUDY. - JEHANI, Dr.Ahmed (مجلة دراسات قانونية, 1977)
We wish to know the value of a foreign judgment, that is, under what conditions and to what extent such a judgment will be effective. The answers to these questions depend upon a country's considerations and policies which determine to what extent it recognizes the foreign country's judgment. The major consideration is international transaction needs. For example, if a person sought enforcement of a judgment in many countries, lack of recognition of the foreign judgment by some of these countries would necessitate multiple law suits and as a consequence higher adjudication costs, the waste of time, and, in some cases, a conflict between judgments from country to country. All of this would disturb the frequency and stability of international transactions.